Reversible and Continuously Tunable Control of Charge of Close Surfaces - Pandey, Rakesh K; Sun, Yajuan; Nakanishi, Hideyuki; Soh, Siowling (The journal of physical chemistry letters, 2017)
Surfaces of almost all types of materials are often charged easily by contact electrification or deposition of ions; hence, surface charge is ubiquitous and has a vast range of influences in our lives and in industry. Since the 19th century, scientists have been measuring the charge of multiple materials collectively. The common expectation is that the total charge of multiple materials is equal to the sum of the charges of the individual materials. This study describes a previously unreported phenomenon in which the total charge of two insulating surfaces decreases when the surfaces are brought close to each other. The charge varies continuously and reversibly depending on the distance of separation between the surfaces. Experimental results derived from analyzing the movement of charge suggest that the changes are due to a rapid exchange of charge between the surfaces and their surrounding air. This change can be used to control the surface charge of the materials flexibly and reversibly.